The Effect Substitution of Soybean Meal with Fermented of Leucaena leaf (Leucaena leucocephala) Flour in the diets on Growth of Baung (Hemibragus nemurus) - Andri Yosia; Adelina '; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on April to May 2009, in the Laboratory of Fish Nutrition and Experimental Pond, Faculty of Fisheries and Marine Science, University of Riau. The purpose of this research are to know the amount of fermented leucaena leaf flour as the alternative feed ingredient on growth of baung (Hemibragus nemurus) with Completely Randomized Design (CRD) was used with five different treatments; P0 (0 : 100%), P1 (10 : 90%), P2 (20 : 80%), P3 (30 : 70%), P4 (40:60%), and three replications. Result indicated that the leucaena leaf flour as the feed ingredient gave significant effect (P < 0.05) on disgebility of diets, feed efficiency, protein retentions, and growth specific. The highest disgebility of diets at P3 (30:70) with 62,96%, effiency feed at P3 (30:70) with 21,12 %, retention protein at P3 (30:70) with 13,45%, growth specific at P3 (30:70) with 1,93%. The quality of the water in the container maintenance temperature of 26-31oC, Dissolved Oxygen levels of 2,8-3.4 ppm, pH of 5-7.Key word : Diet, Growth, Fermented leucaena leaf, Hemibragus nemurus